Twenty-four-hour time-use composition and cognitive function in older adults: cross-sectional findings of the ACTIVate study - Mellow, Maddison L.; Dumuid, Dorothea; Wade, Alexandra T.; Stanford, Ty; Olds, Timothy S.; Karayanidis, Frini; Hunter, Montana; Keage, Hannah A. D.; Dorrian, Jillian; Goldsworthy, Mitchell R.; Smith, Ashleigh E. (Frontiers in Human Neuroscience, 2022)
Physical activity, sedentary behaviour and sleep are associated with cognitive function in older adults. However, these behaviours are not independent, but instead make up exclusive and exhaustive components of the 24-hour day. Few studies have investigated associations between 24-hour time-use composition and cognitive function in older adults. Of these, none have considered how the quality of sleep, or the context of physical activity and sedentary behaviour may impact these relationships. This study investigates how 24-hour time-use composition is associated with cognitive function across a range of domains in healthy older adults, and whether the level of recreational physical activity, amount of television (TV) watching, or the quality of sleep impact these potential associations. 384 healthy older adults (age 65.5 ± 3.0 years, 68% female, 63% non-smokers, mean education = 16.5 ± 3.2 years) participated in this study across two Australian sites (Adelaide, n=207; Newcastle, n=177). Time-use composition was captured using triaxial accelerometry, measured continuously across 7 days. Total time spent watching TV per day was used to capture the context of sedentary behaviours, whilst total time spent in recreational physical activity was used to capture the context of physical activity (i.e., recreational accumulation of physical activity vs other contexts). Sleep quality was measured using a single item from the Pittsburgh Sleep Quality Index. Cognitive function was measured using a global cognition index (Addenbrooke’s Cognitive Examination III) and four cognitive domain composite scores (derived from five tests of the Cambridge Neuropsychological Test Automated Battery: Paired Associates Learning; One Touch Stockings of Cambridge; Multitasking; Reaction Time; Verbal Recognition Memory). Pairwise correlations were used to describe independent relationships between time-use variables and cognitive outcomes. Then, compositional data analysis regression methods were used to quantify associations between cognition and 24-hour time-use composition via isometric log ratios. After adjusting for covariates and false discovery rate there were no significant associations between time-use composition and any cognitive outcomes, and no significant interactions between TV watching time, recreational physical activity engagement or sleep quality and time-use composition for any cognitive outcomes. Future studies should consider investigating these relationships longitudinally to uncover temporal effects.